Weaving place‐based knowledge for culturally significant species in the age of genomics: Looking to the past to navigate the future. (8th April 2022) - Rayne, Aisling; Blair, Stephanie; Dale, Matthew; Flack, Brendan; Hollows, John; Moraga, Roger; Parata, Riki N.; Rupene, Makarini; Tamati‐Elliffe, Paulette; Wehi, Priscilla M.; Wylie, Matthew J.; Steeves, Tammy E.
Abstract: Relationships with place provide critical context for characterizing biocultural diversity. Yet, genetic and genomic studies are rarely informed by Indigenous or local knowledge, processes, and practices, including the movement of culturally significant species. Here, we show how place‐based knowledge can better reveal the biocultural complexities of genetic or genomic data derived from culturally significant species. As a case study, we focus on culturally significant southern freshwater kōura (crayfish) in Aotearoa me Te Waipounamu (New Zealand, herein Aotearoa NZ). Our results, based on genotyping‐by‐sequencing markers, reveal strong population genetic structure along with signatures of population admixture in 19 genetically depauperate populations across the east coast of Te Waipounamu. Environment association and differentiation analyses for local adaptation also indicate a role for hydroclimatic variables—including temperature, precipitation, and water flow regimes—in shaping local adaptation in kōura. Through trusted partnerships between community and researchers, weaving genomic markers with place‐based knowledge has both provided invaluable context for the interpretation of data and created opportunities to reconnect people and place. We envisage such trusted partnerships guiding future genomic research for culturally significant species in Aotearoa NZ and beyond.